Association of Maternal Mental Health and Child Nutritional Status: A Study in Kohalpur Municipality of Banke - Acharya, Lal Mani (Academia Research Journal, 2025)
The main objective of this study is to identify the existing antenatal, natal and post-natal care practices among mothers, their socio-economic and demographic status and the knowledge of respondent on maternal and child health care.  The research was based on descriptive survey research design.  It covers 200 married women (100 from Tharu community and 100 from non-Tharu community) as a sample. The sample was taken with multistage simple random sampling method. Data were collected from the 15-49 years of mothers who have at least one child under the age of five years at the time of survey.  Survey was conducted in the selected household.  Most part of this study has covered the main components of maternal health care practices to find out the status. The relationship between maternal health care and socio-economic and demographic variables were examined by using tabulation. More than one-third of the respondent went for checkup during their pregnancy. Nearly one-third of the respondent know about their pregnancy by urine testing. All the respondents took iron tablets. All the respondent used delivery kit at their delivery. In delivery at home, also new razor blade was the main instrument for cord cutting. All of the mothers fed their infants with colostrum immediately after the baby was born. More than half of the respondent breastfeed their babies until three years. All of the respondent immunized their children. All of the respondents have supplementary food practice to the babies. All of the respondents have immunized their children. One-third of the respondents were suffered from Diarrhoea. The findings of the study show that knowledge and practices of maternal and child health care is satisfactory in this area. To improve the level of practices on maternal and child health care service, the related policies and program be implemented by government. Government should expand the maternal and child health care services. Government should promote for higher education for women, which leads a better maternal and child health care practice in society. Majority of the women were engaged in household activities. Government should most create opportunities for women in various sectors.